Reflections on the identity of nurses in the management of health services (Research, Society and Development, 2022)
Identity is characterized as a process of meaning construction with several interrelated cultural attributes, directing social roles. Regarding the professional identity of nurses, it also takes place from the understanding of their social place and how they project this construction during their academic and professional trajectory, and, in the case of health management, aiming at responses to the needs of nurses. To reflect on the professional identity of health managers nurses. Method: This is a reflective study, carried out in October 2019, in which an unsystematic search was carried out in the literature using the terms 'professional identity', 'professional identity in nursing' and 'professional identity of the health manager and the nurse manager in health', in which the readings of the research conditioned the construction of two chapters: 'Identity of the nursing profession and nursing management - appropriating the history and concepts' and 'Building the professional identity of the nurse manager - from training to practice'. The differential of the nurse's identity in the scope of management must happen through the articulation between care management and the management of people, processes and results. Therefore, a continuous reassessment of the organizational processes and strategies of training institutions is necessary, as it is a challenge to define the necessary competences for the formation of the identity of nurse managers. Conclusion: The professional identity of the nurse manager is formed by reflections of their academic learning towards the relational processes that involve work.